c.2 - Mellor, John W. (New Delhi, 1981)
India is one of the largest and most broadly industrialized of the rising middle powers of the Third World. As such, it has increasing influence on the out come of the major issues of global interdependency: nuc lear proliferation, natural re sources control, trade relations, and population growth. The Western world generally, and the U.S. in particular, remains ill equipped to understand and adapt to this rapidly changing global reality. The topics in this volume were chosen for their importance to under standing the basis of India's global role.
Keywords: Economic assistance